2017
DOI: 10.1111/bju.14076
|View full text |Cite
|
Sign up to set email alerts
|

Defining a glycated haemoglobin (HbA1c) level that predicts increased risk of penile implant infection

Abstract: Uncontrolled DM is associated with increased risk of infection after penile implant surgery. The risk is directly related to the HbA1c level. A threshold HbA1c level of 8.5% is suggested for clinical use to identify patients at increased infection risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…In a recent multi-center, prospective study of 902 implants (76% malleable), patients were stratified into HbA1C groups of <6.5%, 6.5% to 7.5%, 7.6% to 8.5%, 8.6% to 9.5%, and >9.5%, with postoperative infection rates of 1.5%, 6.5%, 14.7%, and 22.4%, respectively. Using a receiver operating characteristic curve, a threshold HbA1c level of 8.5% was identified to indicate increased postoperative risk of IPP infection [33]. We would confer Oxford level of evidence rating 2 for increased risk of postoperative penile prosthesis infection in patients with a perioperative HbA1c >8.5.…”
Section: Patient Factorsmentioning
confidence: 99%
“…In a recent multi-center, prospective study of 902 implants (76% malleable), patients were stratified into HbA1C groups of <6.5%, 6.5% to 7.5%, 7.6% to 8.5%, 8.6% to 9.5%, and >9.5%, with postoperative infection rates of 1.5%, 6.5%, 14.7%, and 22.4%, respectively. Using a receiver operating characteristic curve, a threshold HbA1c level of 8.5% was identified to indicate increased postoperative risk of IPP infection [33]. We would confer Oxford level of evidence rating 2 for increased risk of postoperative penile prosthesis infection in patients with a perioperative HbA1c >8.5.…”
Section: Patient Factorsmentioning
confidence: 99%
“…A multi-centre prospective assessment of preoperative HbA1c levels in more than 900 patients who underwent implant surgery between 2009 and 2015 has recently been reported. 8 The infection rate was significantly higher in those patients with a high HbA1c level, with multivariable analysis identifying a level of 8.5% (~70 mmol/mol) able to predict infection with a sensitivity and specificity of 80% and 65%, respectively. 8 Interestingly, 17 (65.4%) respondents in the current study employed an upper limit that was equal to or higher than this, whilst three (11.5%) did not preclude patients from undergoing implant surgery based upon their diabetic control at all.…”
Section: Discussionmentioning
confidence: 94%
“…In this scenario, it is essential to look at a prospective study designed to predict the importance of Hb1Ac levels at penile prosthesis infection. Habous et al [ 30 ] recently analyzed 902 patients, who received different types of penile prosthesis, and found that Hb1Ac was significantly related to a higher incidence of infection. They had 80 implants with infection, which means an infection rate of 8.9%.…”
Section: Discussionmentioning
confidence: 99%